AB0160 Interferon-Γ-inducible kynurenines inflammation pathway: the missing link between disease activity and symptoms in sjÖgren's syndrome. (15th June 2017) - Valim, V; Sardemberg, WM; Brun, JG; Zandonade, E; Balarini, GM; Tanure, LV; Ferreira, GV; Serrano, ΈV; Tonini, JFV; Brokstad, KA; Ueland, PM; Jonsson, R; et al.
Abstract : Background: Tryptophan (TRYP) can be converted to kynurenine (KYN) by indoleamine 2, 3-dioxygenase (IDO) drived by interferon-γ. Recent studies have suggested that the KYN pathway reflects an important interface between the immune and nervous system modulation. Objectives: The aim was to study KYN pathway and their correlation to clinical and immunological parameters in primary Sjögren's syndrome (pSS). Methods: We included 97 pSS (AECG) and 63 healthy controls matched to age, sex, ethnicity, and body mass index (BMI). KYN metabolites and TRYP were analysed by liquid chromatography mass spectrometry. Results: Patients aged 50±11 years showed anti-SSA-Ro of 63%, anti-SSB-La 31%, anti-nuclear antibody 81%, rheumatoid factor 24%, and systemic manifestations 67%. Most (68%) showed low disease activity measured by Eular Sjögren's Syndrome Disease Activity Index (ESSDAI), 22% moderate and 10% high ESSDAI. The kynurenine:tryptophan ratio (KTR) was (0.031±0.014 vs. 0.024±0.007, p=0.001), KYN (1.890±0.580 vs. 1.652±0.426, p=0.005), quinolinic acid (QA) (477.82±251.55 vs. 382.05±128.06, p=0.018), hydroxikynurenine (3HK) (53.45±52.05 vs. 39.15±9.67, p=0.056), anthranilic acid (AA) (19.86±6.26 vs. 16.78±4.71, p=0.001) were higher while xanthurenic acid (XA) (11.52±7.88 vs.13.00±5.68, p=0.019), and TRYP (64.90±13.43 vs. 71.02±8.88, p=0.012) were lower in pSS compared to controls. Higher KTR was associated with disease duration (r=0.211, p=0.042), CRP (r=0.254, p=0.029), lower hemoglobin (r=-0.219, p=0.34), creatinine (r=0.588, p=0.000), hypergammaglobulinemia (r=0.254, p=0.014), hyper IgG (r=0.354, p=0.004), lower C3 (r=0.262, p=0.011) and C4 (r=-0.294, p=0.004). Higher KTR was observed in those with Biological ESSDAI domain involvement (0.033±0.016 vs. 0.029±0.013, p=0.003), glandular manifestation (0.037±0.014 vs.0.029±0.013, p=0.007), in the other hand lower KTR in those with presence of musculoskeletal pain (0.029±0.011 vs. 0.032±0.015, p=0.003). ESSDAI showed a tendency to correlate with KTR (r=0.177, p=0.091) and ESSPRI inversely correlated with AA (r=-0.233, p=0.071). Either patient with pain showed lower AA (20.66±6.66 vs. 17.22±5.07, p=0.021). Conclusions: TRYP is decreased and KYN metabolites pathway is increased in pSS. IDO activity expressed like KTR was positively correlated with disease activity and glandular manifestations but negatively with pain. A better understanding of the KYN pathway can clear the dissociation of symptoms and disease activity in pSS. References: Maria NI, van Helden-Meeuwsen CG, Brkic Z, et al. Association of Increased Treg Cell LevelsWith Elevated Indoleamine 2, 3-Dioxygenase Activity and an Imbalanced KynureninePathway in Interferon-Positive Primary Sjögren's Syndrome. Arthritis Rheumatol.2016 Jul;68(7):1688–99. Midttun Ø, Hustad S, Ueland PM. Quantitative profiling of biomarkers relatedto B-vitamin status, tryptophan metabolism and inflammation in human plasma byliquid chromatography/tandem mass spectrometry. Rapid Commun Mass Spectrom. 2009 May;23(9):1371–9. Disclosure of Interest: None declared